Prediction of graft length by body height in anatomic double-bundle anterior cruciate ligament reconstruction - Akio Matsumoto; Motoi Yamaguchi; Ken Sasaki; Ryo Kanto (Elsevier, 2018)
To investigate the intra-articular graft length and the length of the bone tunnels after anatomic double-bundle (DB) ACL reconstruction with semitendinosus (ST) tendon, and predict the required length of ST tendon, 178 patients who underwent anatomic DB ACL reconstruction with ST tendon were analyzed. The length of the intra-articular graft was measured by CT. A regression analysis was performed to determine the correlation between the intra-articular graft length and patient height. There was a statistically significant correlation between the intra-articular graft length and patient height. Therefore, the required length of ST tendon can be predicted from patient height. Keywords: Anterior cruciate ligament, Anatomic reconstruction, Graft length, Semitendinosus tendon